Targeted mutagenesis in sea urchin embryos using TALENs. (21st November 2013) - Hosoi, Sayaka; Sakuma, Tetsushi; Sakamoto, Naoaki; Yamamoto, Takashi
<x xml:space="preserve">Abstract</x> Genome editing with engineered nucleases such as zinc‐finger nucleases (ZFNs) and transcription activator‐like effector nucleases (TALENs) has been reported in various animals. We previously described ZFN‐mediated targeted mutagenesis and insertion of reporter genes in sea urchin embryos. In this study, we demonstrate that TALENs can induce mutagenesis at specific genomic loci of sea urchin embryos. Injection of TALEN mRNAs targeting the HpEts transcription factor into fertilized eggs resulted in the impairment of skeletogenesis. Sequence analyses of the mutations showed that deletions and/or insertions occurred at the HpEts target site in the TALEN mRNAs‐injected embryos. The results suggest that targeted gene disruption using TALENs is feasible in sea urchin embryos.